Glass-ceramic coating material for the CO2 laser based sintering of thin films as caries and erosion protection. Issue 9 (September 2017) - Bilandžić, Marin Dean; Wollgarten, Susanne; Stollenwerk, Jochen; Poprawe, Reinhart; Esteves-Oliveira, Marcella; Fischer, Horst
Highlights: Laser-sintering of thin glass-ceramic films on enamel was successfully achieved. Bonding between enamel and the glass-ceramic coating was proved. Method holds great potential to protect susceptible teeth against caries and erosion. Abstract: Objectives: The established method of fissure-sealing using polymeric coating materials exhibits limitations on the long-term. Here, we present a novel technique with the potential to protect susceptible teeth against caries and erosion. We hypothesized that a tailored glass-ceramic material could be sprayed onto enamel-like substrates to create superior adhesion properties after sintering by a CO2 laser beam. Methods: A powdered dental glass-ceramic material from the system SiO2 -Na2 O-K2 O-CaO-Al2 O3 -MgO was adjusted with individual properties suitable for a spray coating process. The material was characterized using X-ray fluorescence analysis (XRF), heating microscopy, dilatometry, scanning electron microscopy (SEM), grain size analysis, biaxial flexural strength measurements, fourier transform infrared spectroscopy (FTIR), and gas pycnometry. Three different groups of samples (each n = 10) where prepared: Group A, powder pressed glass-ceramic coating material; Group B, sintered hydroxyapatite specimens; and Group C, enamel specimens (prepared from bovine teeth). Group B and C where spray coated with glass-ceramic powder. All specimens were heat treated using a CO2 laser beam process. Cross-sections of the laser-sintered specimens were analyzed using laser scanning microscopy (LSM), energy dispersive X-ray analysis (EDX), and SEM. Results: The developed glass-ceramic material (grain size d50 = 13.1 mm, coefficient of thermal expansion (CTE) = 13.3 10 −6 /K) could be spray coated on all tested substrates (mean thickness = 160 μm). FTIR analysis confirmed an absorption of the laser energy up to 95%. The powdered glass-ceramic material was successfully densely sintered in all sample groups. The coating interface investigation by SEM and EDX proved atomic diffusion and adhesion of the glass-ceramic material to hydroxyapatite and to dental enamel. Significance: A glass-ceramic material with suitable absorption properties was successfully sprayed and laser-sintered in thin films on hydroxyapatite as well as on bovine enamel. The presented novel technique of tooth coating with a dental glass-ceramic using a CO2 -laser holds a great potential as a possible method to protect susceptible teeth against caries and erosion.